The inventions, researches, and writings of Nikola Tesla - Martin, Thomas Commerford (Barnes & Noble, 1995)
The Inventions, Researches and Writings of Nikola Tesla is a book compiled and edited by Thomas Commerford Martin detailing the work of Nikola Tesla up to 1893. The book is a comprehensive compilation of Tesla's early work with many illustrations.